POTENSI PETERNAK DAN STRUKTUR POPULASI KERBAU - Harmoko Harmoko; Usman Usman; Zainal Zainal (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2022)
This study aims to determine the potential of breeders and the population structure of buffalo in Lindu sub-district, as information in an effort to increase buffalo productivity in Lindu sub-district. The research sample consisted of 92 breeders and 289 buffaloes, the types of research data were secondary data and primary data, while the data collection techniques used interview techniques, the research data was statistically analyzed and displayed in a frequency table. The results showed that the age range of breeders with the highest proportion was 41-60 years (44.57%) and the lowest was 60 years (27.17%). The education level of breeders with the highest proportion is junior high school education level (46.74%) and the lowest education level is bachelor degree (7.61%). The main occupation of breeders with the highest percentage is in the main occupation of farming (77.17%) and the lowest in the main occupation of civil servants (22.83%). The highest proportion of livestock experience was found in the 1-5 years period (68.48%) and the lowest was in the livestock experience 10 years (9.78%). buffalo population with the highest percentage found in the adult female sex (58.13%) and the lowest in the male sex (2.77%).